Objective analysis of voice in normal young adults - Toran, KC; Lal, BK (Kathmandu University Medical Journal, 2010)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Background: Acoustic vocal parameters measure frequency, intensity (amplitude), perturbation (jitter and shimmer) and dynamic range of the voicing vocal folds. Studies have established that a normal standard data is necessary for acoustic analysis. Objective: The aim of the present study is to standardise Jitter, shimmer, harmonic to noise ratio (HNR) and fundamental frequency (F0) for young adults with normal voice. Materials and methods: Values for acoustic voice measurements were obtained from 50 normal individuals with equal number of sexes, without sign and symptoms of voice problems. The vocal data measurement was performed with Doctor Speech (DRS) Tiger Electronics, USA. Results: Voice analyses were performed with a sustained vowel //i//. The jitter and HNR values were same [1.6 %( ±0.47/±0.43) and 25.8dB (±2.62/±2.72)] for both the genders. For the males, the jitter was 0.14% (±0.02) and 0.16% (±0.04) for female gender. There was a significant difference in the HNR (P=0.000) with 170.05HZ (±32.78) and 246.45HZ (±39.73) respectively for male and female genders. Conclusion: Our results differ from the various literatures; therefore it is important to standardise the program that we use before applying the values for tests designed for a different kind of population. Key words: Acoustic analysis; Perturbation; harmonics to noise ratio; fundamental frequency; standardised voice. DOI: 10.3126/kumj.v7i4.2757 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 374-377